The Name of the Relation: Making a Difference in Aweti Onomastics. Issue 2 (1st June 2019) - Vanzolini, Marina
Abstract : Taking as a starting point an apparently minor event during my fieldwork—the fact that I received an indigenous name from the Aweti, a Tupi-speaking people who inhabit the upper reaches of the Xingu River—this article explores how personal qualities are elicited through names. A presentation of the Aweti onomastic system will highlight its analytical potential to interpret not only the case in question, but also a native theory of descent centered on the familial transmission of chiefdom. Personal names emerge as a way of producing people by evoking specific relations, while simultaneously particularizing the named person. Making a difference from what she or he was before having it, a name operates as a counter-identity device at the same time that it engenders identity qualities.